Some Physical Measurements and Physical Abilities and Their Relationship to Some of The Basketball Skills of Female Students - Halgurd Sherzad Mohammed; Badran Jawhar Qader (QALAAI ZANIST SCIENTIFIC JOURNAL, 2023)
Learn about the relationship of some physical measurements to some of the basketball skills of female students. Learn about the relationship of some physical abilities to some of the basketball skills of female students. Research approach: The researcher used the descriptive approach to suit the nature of the research. The research community represents four-year-old students from the Faculty of Physical Education and Sports Sciences, Salaheddine University for the academic year (2020-2021) in a deliberate manner, numbering (49) female students, while the research sample numbered (15) female students, The researcher used spss to process statistics. - Arithmetic medium, standard deviation and Pearson link coefficient Conclusions: The following conclusions were reached: There is a moral correlation between the length of the kidney body and the length of the upper tip and the width of the hand with the basketball skills of the basketball conversation and correction in the students of basketball There is a moral correlation between everyone who ran 30 meters and pushed a medical ball with the basketball skills of the basketball and correction of the basketball students.